Online determination of state of charge in lithium-ion batteries: influence of the state of health - Armenta-Deu, Carlos (Frontiers in Energy Research, 2025)
This paper focuses on determining the state of charge (SOC) of lithium-ion batteries when they are in operation and the influence that the state of health (SOH) has on SOC determination. The paper studies the effects of the discharge rate on battery performance and evaluation of the SOC. The paper also analyzes the influence of battery aging on the determination of SOC. The online determination of SOC in lithium-ion batteries uses the linear behavior of battery discharge and the influence of the discharge rate on the battery voltage slope. The paper describes a simple algorithm that relates the SOC of the battery with online battery voltage. The proposed measurement method uses a very short controlled discharge at a specific rate that avoids unexpected interferences with the current operation of the battery during states of charge or discharge. We conducted a simulation process to evaluate the evolution of the SOC in Li-ion batteries for different operating stages. Experimental tests validate the proposed methodology, showing a close agreement between theoretical values and experimental results with 98% accuracy. The paper also deals with determining the aging factor in lithium batteries as a critical parameter to calculate the SOC. The method determines the aging factor using a specific simulation for calculating the SOC. The paper compares the results with the values obtained in an experimental test showing high agreement (>93%). The proposed model applies to all lithium-ion batteries and validates for a wide range of battery state-of-health, up to 50%, and with accurate prediction, higher than 90%.